31st Annual Conference of IEEE Industrial Electronics Society, 2005. IECON 2005. 2005
DOI: 10.1109/iecon.2005.1568933
|View full text |Cite
|
Sign up to set email alerts
|

Fast 3D reconstruction for small autonomous robots

Abstract: The reconstruction of the 3D structure of a static env ironm ent is a p ow erful cap ab ility ap p licab le to rob ot nav ig ation. W e p resent a nov el ap p roach to d eterm ine the 3D p ositions of a sp arse set of p oints track ed b y a sm all autonom ous rob ot in a static env ironm ent. U sing noisy feature track ing and a roug h estim ate of the essential m atrix , our m ethod has a relativ ely low com p utational cost and runs at fram e rate (1 5 fp s) on a sm all F P G A -b ased rob ot p latform . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
10

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
3
0
10
Order By: Relevance
“…Their highly parallel architecture with low power consumption, small size and weight provide an excellent platform for achieving realtime performance on this type of applications. Several authors [19], [20], [21], [22], [23], [24] reported successful implementation of robotic vision algorithms on FPGA-based hardware. Despite existing guidelines, methods and tools for FPGAs aimed at shortening the design cycle [25], [26], [27], [28], the main drawback of FPGA-based methods is time consuming implementation.…”
Section: Embedded Solutionmentioning
confidence: 99%
“…Their highly parallel architecture with low power consumption, small size and weight provide an excellent platform for achieving realtime performance on this type of applications. Several authors [19], [20], [21], [22], [23], [24] reported successful implementation of robotic vision algorithms on FPGA-based hardware. Despite existing guidelines, methods and tools for FPGAs aimed at shortening the design cycle [25], [26], [27], [28], the main drawback of FPGA-based methods is time consuming implementation.…”
Section: Embedded Solutionmentioning
confidence: 99%
“…denota o passo limiar da equação (3)(4)(5)(6)(7)(8)(9)(10). Tais passos são perfeitamente implementáveis numa GPU por fragmentos apropriados utilizando dois passos de renderização.…”
Section: 22unclassified
“…Tais passos são perfeitamente implementáveis numa GPU por fragmentos apropriados utilizando dois passos de renderização. A primeira etapa implementa os passos 1a e 1b da equação (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Os valores v k+1 são utilizados somente temporariamente no programa shader e não precisam ser armazenados.…”
Section: 22unclassified
See 2 more Smart Citations